2018
DOI: 10.1016/j.foodchem.2017.12.058
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of anthocyanins from bilberries – Effects on bioavailability and intestinal accessibility in humans

Abstract: Anthocyanins are flavonoids that have been suggested to provide beneficial health effects. The biological activity of anthocyanins is influenced by their pharmacokinetic properties, but anthocyanins are associated with limited bioavailability in humans. In the presented study, we investigated how the encapsulation of bilberry extract (BE), a source of anthocyanins, with either whey protein or citrus pectin influences the bioavailability and intestinal accessibility of anthocyanins in humans. We performed an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 35 publications
1
58
0
Order By: Relevance
“…Indeed, in vitro studies demonstrated that nanocomplexes with chitosan hydrochloride, carboxymethyl chitosan and β-lactoglobulin may favor the bioavailability of anthocyanins in a simulated gastrointestinal tract [ 120 ]; that bilberry anthocyanins encapsulated in liposomal micelles were more bioavailable at the cellular level in vitro; and that their efficacy as anticancer agents was significantly higher than that of non-encapsulated anthocyanins [ 121 ]. However, a recent paper by Mueller et al [ 122 ], in which the anthocyanins were encapsulated in whey proteins, demonstrated that this formulation had little effect on the stabilization of anthocyanins during intestinal passage, and increased the rate of degradation when compared to non-encapsulated anthocyanins. The authors hypothesized that whey protein encapsulation might increase systemic concentrations and short-term bioavailability by prolonging the duration of stomach passage, leading to higher concentrations of anthocyanins and their degradation products in urine.…”
Section: Anthocyanins In Foodmentioning
confidence: 99%
“…Indeed, in vitro studies demonstrated that nanocomplexes with chitosan hydrochloride, carboxymethyl chitosan and β-lactoglobulin may favor the bioavailability of anthocyanins in a simulated gastrointestinal tract [ 120 ]; that bilberry anthocyanins encapsulated in liposomal micelles were more bioavailable at the cellular level in vitro; and that their efficacy as anticancer agents was significantly higher than that of non-encapsulated anthocyanins [ 121 ]. However, a recent paper by Mueller et al [ 122 ], in which the anthocyanins were encapsulated in whey proteins, demonstrated that this formulation had little effect on the stabilization of anthocyanins during intestinal passage, and increased the rate of degradation when compared to non-encapsulated anthocyanins. The authors hypothesized that whey protein encapsulation might increase systemic concentrations and short-term bioavailability by prolonging the duration of stomach passage, leading to higher concentrations of anthocyanins and their degradation products in urine.…”
Section: Anthocyanins In Foodmentioning
confidence: 99%
“…Anthocyanin content is considered an important quality component due to the attributed antioxidant activity of these compounds. The antioxidant activity of anthocyanin in blood orange fruits is useful for human health, with an impact on some diseases, including anti-inflammatory, anticancer, and antidiabetic, due to the prevention of oxidation and free-radical chain reactions [ 5 , 6 , 7 , 8 , 9 ]. In blood oranges, 10 anthocyanins were previously identified [ 6 , 10 ], with the major anthocyanins in the flesh being cyanidin 3-glucoside and cyanidin 3-(6″-malonylglucoside) [ 1 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies suggest that the consumption of anthocyanins contributes to maintaining human health and lowering the risk of diabetes, arthritis, and cancer; these effects are due, at least in part, to their antioxidant and anti-inflammatory activities [10]. Besides, given the many interesting biological activities, pigmented foods have a huge potential for the extraction of natural colorants and antioxidants, which are useful for developing new nutraceuticals [11]. Many in vitro studies have revealed the potential beneficial health effects of pigmented tuber extracts [3,6,7].…”
Section: Introductionmentioning
confidence: 99%